Comparison of High, Intermediate, and Low Frequency Shock Wave Lithotripsy for Urinary Tract Stone Disease: Systematic Review and Network Meta-Analysis. - Dong Hyuk Kang; Kang Su Cho; Won Sik Ham; Hyungmin Lee; Jong Kyou Kwon; Young Deuk Choi; Joo Yong Lee (PLoS ONE, 2016)
Objectives To perform a systematic review and network meta-analysis of randomized controlled trials (RCTs) to determine the optimal shock wave lithotripsy (SWL) frequency range for treating urinary stones, i.e., high-frequency (100-120 waves/minute), intermediate-frequency (80-90 waves/minute), and low-frequency (60-70 waves/minute) lithotripsy. Materials and methods Relevant RCTs were identified from electronic databases for meta-analysis of SWL success and complication rates. Using pairwise and network meta-analyses, comparisons were made by qualitative and quantitative syntheses. Outcome variables are provided as odds ratios (ORs) with 95% confidence intervals (CIs). Results Thirteen articles were included in the qualitative and quantitative synthesis using pairwise and network meta-analyses. On pairwise meta-analyses, comparable inter-study heterogeneity was observed for the success rate. On network meta-analyses, the success rates of low- (OR 2.2; 95% CI 1.5-2.6) and intermediate-frequency SWL (OR 2.5; 95% CI 1.3-4.6) were higher than high-frequency SWL. Forest plots from the network meta-analysis showed no significant differences in the success rate between low-frequency SWL versus intermediate-frequency SWL (OR 0.87; 95% CI 0.51-1.7). There were no differences in complication rate across different SWL frequency ranges. By rank-probability testing, intermediate-frequency SWL was ranked highest for success rate, followed by low-frequency and high-frequency SWL. Low-frequency SWL was also ranked highest for low complication rate, with high- and intermediate-frequency SWL ranked lower. Conclusions Intermediate- and low-frequency SWL have better treatment outcomes than high-frequency SWL when considering both efficacy and complication.